Implementing Scientific Inquiry Learning in Rural Areas: Understanding Students' Needs to Train Inquiry Skills in Dynamic Electricity - Sumardani, Nur Ichsan; Prima, Eka Cahya; Rusdiana, Dadi (Journal of Teaching and Learning Physics, 2024)
The development of digital technology has become a phenomenon that not only changes how we interact with the world but also creates social segregation affecting both advanced and underdeveloped countries, as well as rural and remote areas. The COVID-19 pandemic has accelerated digital adaptation worldwide, emphasizing the importance of digital literacy. To compensate for this situation, ADDIE development research was conducted to address the needs of students. First, the research conducted an analytical survey of 400 middle school students to explore their scientific interests and digital literacy in the Lebak Regency, which had previously been identified as one of the underdeveloped areas in Indonesia but had shed that status in 2019. The analysis revealed that 99% of students had used electronic devices daily. However, only 69% of students used them in an educational context within the classroom. Additionally, the analysis showed that 62% of respondents spent 1-2 hours per day learning activities online, while 30% reported spending more than 6 hours for purposes other than studying. Perceptions of science also indicated high interest (56%), but confusion about concepts still occurred in the classroom, leading to 55% of students not fully understanding the material after completing the class. The research attempted to design web-based learning media as modules to address these challenges. The resulting design was implemented using Google Sites in the form of inquiry-based activities accessible through www.belajarinkuiri.com. In conclusion, the development of web-based e-modules proved to be an effective method to meet the needs of students in the Lebak Regency, Banten, and is worthy of experimentation in the implementation phase. Thus, efforts to address digital literacy challenges and enhance scientific literacy in the era of globalization can be tackled.